The Causal Relationship Between Tax Revenue And Government Expenditure In Syria For The Period (1985-2015) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
This study aimed to examine the causal relationship between tax revenues and current and investment government expenditures in Syria for the period (1985-2010), and to clarify the impact of the Syrian crisis on the nature and direction of this relationship. The stability of time series was initially tested using the modified Dickey Fuller test and the Phillips Peron test, Then Johansen test for co-integration to reach the long-term relationship between variables, the short-term relationship was tested by error correction model, and finally causality between variables was tested using Granger causality. The results showed that there is a positive relationship between tax revenues and government current and investment spending in the long term, while in the short term there is a relationship between current spending and tax revenues, and absence of this relationship between investment spending and tax revenues. The results of causation showed a two-way causal relationship between current expenditure and tax revenues, while there was no causality between investment spending and tax revenues. The Syrian crisis also has an impact on the nature and direction of this relationship, as demonstrated by the potential value of the crisis factor هدفت هذه الدراسة إلى اختبار العلاقة السببية بين الإيرادات الضريبية والنفقات الحكومية الجارية والاستثمارية في سورية للفترة (1985-2015)، وكذلك توضيح أثر الأزمة على طبيعة واتجاه هذه العلاقة. حيث تم في البداية اختبار استقرارية السلاسل الزمنية باستخدام اختبار ديكي فوللر المعدل Augmented Dickey-Fuller واختبار فيليبس بيرون Phillips- Perron. ومن ثم اختبار جوهانسن للتكامل المشترك Johansen cointegration للوصول إلى العلاقة طويلة الأجل بين المتغيرات، أما العلاقة قصيرة الأجل فتم اختبارها عن طريق نموذج تصحيح الخطأ Error Correction Model، وأخيرا" تم اختبار السببية بين المتغيرات باستخدام جرانجر للسببية Granger causality. بينت النتائج وجود علاقة موجبة بين الإيرادات الضريبية والإنفاق الحكومي الجاري والاستثماري في الأجل الطويل، بينما في الأجل القصير فهناك علاقة بين الإنفاق الجاري والإيرادات الضريبية، وغياب هذه العلاقة بين الإنفاق الاستثماري والإيرادات الضريبة. أما نتائج السببية بينت وجود علاقة سببية ثنائية الاتجاه بين الإنفاق الجاري والإيرادات الضريبية، بينما عدم وجود سببية بين الإنفاق الاستثماري والإيرادات الضريبية. كما أن للأزمة السورية أثر على طبيعة واتجاه هذه العلاقة وهذا ما وضحته القيمة الاحتمالية لمعامل الأزمة.